Evaluation of dimensional accuracy on SLM product using 3D laser scanner - Moch. Agus Choiron; Anindito Purnowidodo; Achfas Zacoeb; Rosadila Febritasari; Willy Artha Wirawan; Imam Kusyairi; Johan Wayan Dika (Mechanical Engineering for Society and Industry, 2025)
Dimensional accuracy is a critical factor in additive manufacturing, especially in Selective Laser Melting (SLM). Recently, many studies had investigated the SLM process and products, but studies on the evaluation of SLM printing product to check the dimensional accuracy have not been explored. This study investigates the dimensional accuracy of SLM products by employing a 3D laser scanning technology and evaluate the compatibility between CAD designs and the final SLM printed products. The 3D laser scanning is performed using a high-precision 3D laser scanner, then continued by comparison with the CAD model through Geomagic Control X software. Dimensional accuracy was measured using visual and statistical parameters such as color graphic and deviation. Results showed that deviation of SLM printed products was within the tolerance range of ±0.1 mm. The main factors that affect accuracy are printing laser speed and print orientation. The 3D laser scanning technology proved to be effective for evaluating the dimensional accuracy of SLM printed products. This study contributes to develop the quality control methods in the field of metal-based additive manufacturing.